A comprehensive corpus-based analysis of “X Auxiliary Subject” constructions in written and spoken English - Prado-Alonso Carlos (Topics in Linguistics, 2019)
This paper describes a corpus-based analysis of subject-auxiliary inversion in both spoken and written English. The focus of the analysis is Chen’s (2013) X Auxiliary Subject construction (XASC), where X codes the fronting of a constituent which triggers the inversion of the auxiliary and the subject, as in “Never has trade union loyalty faced a more baffling test” or “What did he do?” On the basis of a statistical analysis using corpora of written and spoken English, it is argued that the distribution of XAS inversion, in the interrogative mood, is related to the degree of an addressor’s involvement in a text. It will be shown that, in the interrogative mood, the more involvement in a text, the more XAS inversions are to be expected. It is also argued that XAS inversions in interrogative clauses can be seen to serve as discourse markers through which an addressor’s involvement is coded in written and spoken English discourse. The analysis will also show that XAS inversions in the declarative mood also serve an interpersonal function, this, however, being inherently tied to the clause-linking function performed by the construction. Furthermore, the data will show that the distribution of XAS inversions in declarative clauses is related to the degree of informational content of the texts in which these inversions occur.